a) x4 + 16                            b) x<...">
K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

20 tháng 10 2021

b) \(x^4y^4+64\)

\(=\left(x^4y^4+16x^2y^2+64\right)-16x^2y^2\)

\(=\left(x^2y^2+8\right)^2-\left(4xy\right)^2\)

\(=\left(x^2y^2-4xy+8\right)\left(x^2y^2+4xy+8\right)\)

c) \(x^4y^4+4\)

\(=\left(x^4y^4+4x^2y^2+4\right)-4x^2y^2\)

\(=\left(x^2y^2+2\right)^2-\left(2xy\right)^2\)

\(=\left(x^2y^2-2xy+2\right)\left(x^2y^2+2xy+2\right)\)

3 tháng 9 2018

\(x^2-2x-4y^2-4y\)

\(=\left(x^2-4y^2\right)-\left(2x+4y\right)\)

\(=\left(x-2y\right)\left(x+2y\right)-2\left(x+2y\right)\)

\(=\left(x+2y\right)\left(x-2y-2\right)\)

1 tháng 10 2020

\begin{array}{l} a){\left( {ab - 1} \right)^2} + {\left( {a + b} \right)^2}\\  = {a^2}{b^2} - 2ab + 1 + {a^2} + 2ab + {b^2}\\  = {a^2}{b^2} + 1 + {a^2} + {b^2}\\  = {a^2}\left( {{b^2} + 1} \right) + \left( {{b^2} + 1} \right)\\  = \left( {{a^2} + 1} \right)\left( {{b^2} + 1} \right)\\ c){x^3} - 4{x^2} + 12x - 27\\  = {x^3} - 27 + \left( { - 4{x^2} + 12x} \right)\\  = \left( {x - 3} \right)\left( {{x^2} + 3x + 9} \right) - 4x\left( {x - 3} \right)\\  = \left( {x - 3} \right)\left( {{x^2} + 3x + 9 - 4x} \right)\\  = \left( {x - 3} \right)\left( {{x^2} - x + 9} \right)\\ b){x^3} + 2{x^2} + 2x + 1\\  = {x^3} + 2{x^2} + x + x + 1\\  = x\left( {{x^2} + 2x + 1} \right) + \left( {x + 1} \right)\\  = x{\left( {x + 1} \right)^2} + \left( {x + 1} \right)\\  = \left( {x + 1} \right)\left( {x\left( {x + 1} \right) + 1} \right)\\  = \left( {x + 1} \right)\left( {{x^2} + x + 1} \right)\\ d){x^4} - 2{x^3} + 2x - 1\\  = {x^4} - 2{x^3} + {x^2} - {x^2} + 2x - 1\\  = {x^2}\left( {{x^2} - 2x + 1} \right) - \left( {{x^2} - 2x + 1} \right)\\  = \left( {{x^2} - 2x + 1} \right)\left( {{x^2} - 1} \right)\\  = {\left( {x - 1} \right)^2}\left( {x - 1} \right)\left( {x + 1} \right)\\  = {\left( {x - 1} \right)^3}\left( {x + 1} \right)\\ e){x^4} + 2{x^3} + 2{x^2} + 2x + 1\\  = {x^4} + 2{x^3} + {x^2} + {x^2} + 2x + 1\\  = {x^2}\left( {{x^2} + 2x + 1} \right) + \left( {{x^2} + 2x + 1} \right)\\  = \left( {{x^2} + 2x + 1} \right)\left( {{x^2} + 1} \right)\\  = {\left( {x + 1} \right)^2}\left( {{x^2} + 1} \right) \end{array}

21 tháng 10 2021

\(\left(x+5\right)\left(x^2-5x+25\right)\)

\(=\left(x+5\right)\left(x^2-5.x+5^2\right)\)

\(=x^3+5^3\)

\(=x^3+125\)

21 tháng 10 2021

3) \(27-y^3\)

\(=3^3-y^3\)

\(=\left(3-y\right)\left(9-3y+y^2\right)\)

10 tháng 8 2021

Trả lời:

a) \(\frac{1}{4}x^2y+5x^3-x^2y^2=x^2\left(\frac{1}{4}y+5x-y^2\right)\)

 b) 5x ( x - 1 ) - 3y ( 1 - x ) = 5x ( x - 1 ) + 3y ( x - 1 ) = ( x - 1 )( 5x + 3y )

 c) 4x- 25 = ( 2x )2 - 52 = ( 2x - 5 )( 2x + 5 )

 d) 6x- 9x2 = 3x ( 2 - 3x )

25 tháng 7 2021

Ta có: a + b + c = 0

<=> a2 + b2 + c2 + 2(ab + bc + ac) = 0

<=> a2 + b2 + c2 = -2(ab + bc + ac)

<=> a4 + b4 + c4 + 2(a2b2 + b2c2 + a2c2 = 4[a2b2 + b2c2 + a2c2 + 2abc(a + b + c)] (vì a + b + c= 0)

<=> a4 + b4 + c4 + 2(a2b2 + b2c2 + a2c2) = 4(a2b2 + b2c2 + a2c2)

<=> a4 + b4 + c4 = 2(a2b2 + b2c2 + a2c2) (đpcm)

b) Từ a4 + b4 + c4 = 2(a2b2 + b2c2 + a2c2)

<=> (a4 + b4 + c4)/2 = a2b2 + b2c2 + a2c2 + 2abc(a + b + c) (vì a + b + c) = 0

<=> (a4 + b4 + c4)/2 = (ab + bc + ac)2

<=> a4 + b4 + c4 = 2(ab + bc + ac)2 (đpcm)

c) Từ a4 + b4 + c4 = 2(a2b2 + b2c2 + a2c2)

<=> 2(a4 + b4 + c4) = a4+ b4 + c4 + 2(a2b2 + b2c2 + a2c2)

<=> 2(a4 + b4 + c4) = (a2 + b2 + c2)2

<=> a4 + b4 + c4 = (a2 + b2 + c2)2/2 (đpcm) 

24 tháng 8 2021

Trả lời:

a, \(-xy.\left(x^2+2xy-3\right)=-x^3y-2x^2y^2+3xy\)

b, \(\left(12x^6y^5-3x^3y^4+4x^2y\right):6x^2y\)

\(=12x^6y^5:6x^2y^2-3x^3y^4:6x^2y+4x^2y+6x^2y\)

\(=2x^4y^3-\frac{1}{2}xy^3+\frac{2}{3}\)

NM
24 tháng 8 2021

a.\(\left(-xy\right)\left(x^2+2xy-3\right)=-x^3y-2x^2y^2+6xy\)

b.\(\left(12x^6y^5-3x^3y^4+4x^2y\right):6x^2y=2x^4y^4-\frac{1}{2}xy^3+\frac{2}{3}\)

28 tháng 11 2021

g) \(x^5-3x^4+3x^3-x^2=x^2\left(x^3-3x^2+3x-1\right)=x^2\left(x-1\right)^3\)

f) \(x^2-25-2xy+y^2=\left(x^2-2xy+y^2\right)-25=\left(x-y\right)^2-5^2=\left(x-y-5\right)\left(x-y+5\right)\)

e) \(16x^3+54y^3=2\left(8x^3+27y^3\right)=2\left[\left(2x\right)^3+\left(3y\right)^3\right]=2\left(2x+3y\right)\left(4x^2-6xy+9y^2\right)\)

d) \(3y^2-3z^2+3x^2+6xy=3\left(x^2+2xy+y^2-z^2\right)=3\left[\left(x+y\right)^2-z^2\right]=3\left(x+y+z\right)\left(x+y-z\right)\)